German nuclear phase-out policy: Effects on European electricity wholesale prices, emission prices, conventional power plant investments and eletricity trade - Thure Traber; Claudia Kemfert (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The German decision to finally phase-out nuclear electricity has led to a debate on its effects on electricity prices, emission prices in the European emission trading system, as well as on international electricity trade. We investigate these effects with a Electricity market model for Europe with investments in power plants under oligopolistic conditions in Germany. We find modest price increases on the German wholesale market by the mid-term 2020 and an effect of the accelerated nuclear phase- out of between four and twelve percent. Moreover, the increase in the emission allowance prices due to the change in nuclear policy is between 1:8 and 3 Euro per ton of CO2 by the same period. The large variations in our results are induced by four combinations of the European emission trading policy and the success of the German energy efficiency policy. Most pronounced price effects are found in scenarios with a successful energy savings policy, which acts as a substitute for new power plants. Moreover, the tighter the emission trading system is, the larger are the effects of the accelerated phase-out on electricity and emission prices. Under a tight system, however, investments in conventional generation are likely to be dominated by natural gas fired plants since the decrease of utilization rates induced by renewable energies are more important for coal fired power plants with their relative high investment costs.
Keywords: C63; L13; L94; Q38; 330; energy modeling; nuclear phase-out; climate policy; oligopoly